Implementation of Bayes Network in Giving First Aid Solution - Darien Daud Earlliawand; Tjong Wan Sen (IT for Society, 2016)
In a critical situation, such as traffic accident, sometimes a person is required to do a first aid in order to save someone’s life, until the emergency unit arrives. If a person does not know how to do a first aid, he or she will need a guide, such as an application in a device that people always bring, a smartphone. Technology is one of the science fields that grow very fast. It is not only about the hardware but also the software, such as artificial intelligence. Artificial intelligence is one of the fields that are commonly used nowadays, either for gaming purpose, education and research purpose, or other purposes. This application, ES First Aid, is an Android application to help the user to decide what to do in emergency situation. It will ask a few questions related to the condition of the casualty then it will tell the user clearly about the actions needed to be taken.